Fishes of La Venta River in Chiapas, Mexico - González-Díaz, Alfonso Ángel; Quiñones, Rebecca María; Velázquez-Martínez, José (Zootaxa, 2008)
Although Chiapas is recognized as home to some of the most interesting fishes in Mexico, there are still regions of the state that are poorly surveyed. Our objective was to document the fish species in La Venta River, as well as that of some of its largest tributaries and Netzahualc\yotl Reservoir. To this aim, field collections were made during three consecutive years and preserved specimens from the ichthyological collection at El Colegio de la Frontera Sur, San Crist\bal, Chiapas were reviewed. We identified 42 species including new records for the state of Chiapas (3 species), the Grijalva River watershed (3 species), and Netzahualc\yotl Reservoir (2 species). Species composition differed between the upper and lower portions of La Venta River, most likely due to historical factors, and the physical and chemical differences between the two areas. The species composition of the upper parts of La Venta River was distinctive within the watershed but  similar to neighboring hydrologic systems, suggesting that this area was recently connected to other rivers. Our results revealed that the Grijalva River-Tuxtla GutiJrrez watershed is species rich and may be important for describing the distribution patterns of several groups of fishes in Mexico